Development and Validation of a Stability-Indicating Reversed-Phase Ultra High Pressure Liquid Chromatography Method for Assay of Delmopinol Hydrochloride and Estimation of Its Related Substances in Commercial Bulk Batches. (11th December 2021) - Zhuang, Jinyou; Rustum, Abu M
Abstract: Delmopinol hydrochloride is widely used as an active ingredient (AI) in many human oral hygiene products. To the best of our knowledge (via literature search), there is no stability-indicating liquid chromatography method available in the public domain for assay and estimation of related substances of Delmopinol hydrochloride. A fast stability-indicating Reversed-Phase Ultra High-Performance Liquid Chromatography (RP-UHPLC) method has been developed and validated for identification, assay and estimation of related substances in commercial bulk batches of this AI. The major peak of the AI and its related compounds are adequately separated in 6 min by a gradient elution on a hybrid silica-based C18 column (Waters Acquity UPLC® BEH C18, 50mm × 2.1 mm I.D., 1.7 μm particle size) maintained at 50°C. Mobile phase-A is composed of aqueous 10 mM NH4 OH and mobile phase-B is ACN. The AI and its related compounds are detected with UV detection at 220 nm and quantitated by an external Delmopinol hydrochloride reference standard. The quantitation limit of the method is 0.1% of the target analytical concentration. This UHPLC method is fast and green and has been demonstrated to be specific, accurate, linear, precise, sensitive and robust as per ICH guidelines.